2018
DOI: 10.5114/pjr.2018.76007
|View full text |Cite
|
Sign up to set email alerts
|

Application of the apparent diffusion coefficient in magnetic resonance imaging in an assessment of the early response to treatment in Hodgkin’s and non-Hodgkin’s lymphoma – pilot study

Abstract: PurposeLymphoproliferative neoplasms are the largest and most frequently diagnosed entities in the group of haematological malignancies. The aim of the study was to assess whether apparent diffusion coefficient (ADC) measured on the first day of the second cycle of chemotherapy could be a predictor of prognosis and of the final treatment’s outcome.Material and methodsThe study included 27 patients with diagnosed Hodgkin’s and non-Hodgkin’s lymphoma, who had magnetic resonance (MR) performed with diffusion weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…Two former studies have focused on the role of ADC in predicting outcome in systemic lymphoma, but the results are discordant. In line with our results, a study of 39 patients with HL found that disease sites with an inadequate treatment response had significantly higher pretreatment ADC [ 15 ], while a pilot study including 27 patients with HL and NHL found that patients with ADC > 752 mm 2 /s before treatment had a lower probability of progression [ 25 ]. The reason for this discrepancy is hard to postulate.…”
Section: Discussionsupporting
confidence: 87%
“…Two former studies have focused on the role of ADC in predicting outcome in systemic lymphoma, but the results are discordant. In line with our results, a study of 39 patients with HL found that disease sites with an inadequate treatment response had significantly higher pretreatment ADC [ 15 ], while a pilot study including 27 patients with HL and NHL found that patients with ADC > 752 mm 2 /s before treatment had a lower probability of progression [ 25 ]. The reason for this discrepancy is hard to postulate.…”
Section: Discussionsupporting
confidence: 87%
“…Among the 15 PET/CT-positive patients (DS 4-5), 3 of them (n. 14,19,21) were also considered MRI-positive (PET+/MRI+ and all 3 had high SUV max values (8; 17.4; 25) and low ADC values (0.9; 1.2; 0.8) with a median value of 0.90 mm 2 /s (Fig. 3): due to the high radiological suspicion of residual disease these 3 patients underwent to mediastinal biopsy for histological confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…To improve post-treatment response assessment, other instrumental investigations, such as diffusion weighted magnetic resonance imaging (DW-MRI), may be added. Actually, DW-MRI is a promising radiation-free technique for staging and following-up many types of neoplasms including lymphomas [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[11]. Die diffusionsgewichtete Bildgebung zeigt vielversprechende Ergebnisse zur Abschätzung eines Therapieansprechens [33].…”
Section: Schilddrüseunclassified